THE EFFECT OF THE D185 MUTATION ON THE STABILITY AND FUNCTIONALITY OF RUBISCO LIKE PROTEIN (RLP) FROM CHROMOHALOBACTER SALEXIGEN BKL 5 - Sudarmanto, I.; Rohman, M. S.; Artama, W. T. (Jurnal Kimia (Journal of Chemistry); Vol. 18, No.1, Januari 2024, 2024)
In the case of Rubisco Like Protein (RLP)  Chromohalobacter salexigen  BKL 5 (RLP CS), which is halophilic, the presence of salt bridges (SB) is not too numerous but efficient enough to maintain stability in high salt stress. This study was to determine the effect of mutations SB at position 185 (D185/WT) on the stability and activity of RLP CS through an in-silico approach by replacing aspartic acid with glutamic acid and alanine (D185E and D185A). The methods used were Molecular Dynamics Simulations (MDS) and Molecular Docking (MD). The MDS was used to study molecular characteristics at the atomic level, while MD was for the interaction patterns of proteins and ligands. The results of the MDS analysis carried out at 10ns showed that the mutation at position 185 with alanine and glutamic acid changed the size/dimensional of RLP CS and affected its overall geometric structure. Interestingly, even though the structure has changed, the activity of the protein remains relatively constant, which is indicated by the results of MD, and has a relatively similar binding energy value of around -6.3 Kcal/mol.  Keywords : Chromohalobacter salexigen BKL 5, molecular docking, molecular dynamic simulation, mutation, saltbridge